Il mondo in subbuglio ricerche sull'età delle rivoluzioni (1789-1849) - Dinacci, Marcello; Maione, Domenico (Clio. Saggi di scienze storiche, archeologiche e storico-artistiche, 2022)
The aim of this publication is to discuss the revolutions phenomenon and its multi-faceted development on a large geographic scale and a long-term perspective. The 25 essays included concern studies from territorial legislation and administration studies to political debates; from conspiracy strategies to economic, cultural, social, religious, communicational and artistic matters. Such papers are to be considered an effort to synthetize the most recent historiographic perspectives, result of wide and inclusive academic discussions about the great turmoil of 1789-1849. The purpose is to provide new contributions to the current international debate on the revolutionary and counterrevolutionary movements of that period.